1997
DOI: 10.1099/00222615-46-5-360
|View full text |Cite
|
Sign up to set email alerts
|

Moraxella (Branhamella) catarrhalis - clinical and molecular aspects of a rediscovered pathogen

Abstract: Since its discovery at the end of the nineteenth century, Moraxella (Branhamella) catarrhalis has undergone several changes of nomenclature and periodic changes in its perceived status as either a commensal or a pathogen. Molecular analysis based on DNA hybridisation or 16s rDNA sequence comparisons has established its phylogenetic position as a member of the Moraxellaceae and shown that it is related more closely to Acinetobacter spp. than to the genus Neisseria in which it was placed formerly. However, confu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
96
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 108 publications
2
96
0
1
Order By: Relevance
“…In the late 1990s, Enright and McKenzie suggested that the M. catarrhalis species has a population structure similar to that of N. meningitidis, which possesses a nonclonal (panmictic) population due to its high rate of genomic recombination, with an occasional emergence of successful clones (38). Subsequent MLST of N. meningitidis yielded 47 sequence types (STs) from 92 strains (128), and for M. catarrhalis, 173 MLST STs were observed among 268 isolates (153).…”
Section: Heterogeneity Of the M Catarrhalis Speciesmentioning
confidence: 99%
“…In the late 1990s, Enright and McKenzie suggested that the M. catarrhalis species has a population structure similar to that of N. meningitidis, which possesses a nonclonal (panmictic) population due to its high rate of genomic recombination, with an occasional emergence of successful clones (38). Subsequent MLST of N. meningitidis yielded 47 sequence types (STs) from 92 strains (128), and for M. catarrhalis, 173 MLST STs were observed among 268 isolates (153).…”
Section: Heterogeneity Of the M Catarrhalis Speciesmentioning
confidence: 99%
“…A total of 281 isolates were BRO-1, and 19 were BRO-2 (including one ATCC strain). Two strains had MICs to benzylpenicillin and ampicillin elevated above those of the wild type, suggesting the presence of either ␤-lactamases other than those of the BRO type (14) or polymorphisms in BRO genes preventing PCR amplification.…”
Section: Resultsmentioning
confidence: 99%
“…If the isolate comes from blood or another sterile body site culture (e.g., pleural fluid), treatment is clearly warranted. The organism is believed to be the third most common bacterium associated with acute exacerbations of chronic bronchitis and acute otitis media (4,5,14), both of which require antimicrobial treatment under certain circumstances. If resistance to commonly recommended agents is emerging, then regular testing would also be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogen, also known as Micrococcus catarrhalis, Neisseria catarrhalis and Brahamella catarrhalis, is a clinically important pathogen and is a common cause of respiratory infections, particularly otitis media in children and lower respiratory tract infection in elderly patients [2][3][4][5]. M. catarrhalis is considered to be the third most common and most important cause of bronchopulmonary infections after Streptococcus pneumoniae and Haemophilus influenzae [6,7]. In the Alexander project in Europe and the US between 1992 and 1993, M. catarrhalis was identified in 13.5% of bacterial isolates [8].…”
mentioning
confidence: 99%